Social Education of Children with Developmental Disabilities in Yenisei Siberia During the Formation of the Soviet State: Practical Experience - U. Kolokolnikova, Zulfiya; B. Lobanova, Olga; A. Mosina, Natalia; V. Basalaeva, Natalia; V. Gazizova, Tatiana; A. Kolesnikova, Tatiana (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of the analysis of historical and pedagogical literature and archival materials. A review of documents and materials related to the organization of social education of children with developmental disabilities in the 20s and 30s of the 20th century was performed. It is proved that in the Russian science of the 20s of the 20th century there was no unambiguous definition for designating children with developmental disabilities as a special category; special attention was paid to the foundation of social education institutions for “physically defective and mentally retarded” children in the 20s-30s -s of the 20th century not only in the central part of the country but also in the regions. The problems of the practice of organizing social education of children with developmental disabilities (physically defective and mentally retarded) in Yenisei Siberia in the 20s-30s -s of the 20th century are considered. It was shown that social education institutions for this category of children included boarding schools for deaf-mute children and schools for physically defective children; in general, the development of the practice of social education in institutions for “defective” children in Yenisei Siberia followed the methods of improving the methods of teaching communication and mastering general labor and primary professional skills, which confirmed the optimistic position of the state on the inclusion of every child in public life. It has been proved that the process of social education in Yenisei Siberia in the 1920s-1930s was characterized by specific to the Siberian region trends of development (the late development of the social education system, lack of special (correctional) educational institutions in the region, insufficient development of early diagnosis services, and the lack of qualified personnel, etc.). It is proved that the appeal to the historical experience of the development of a special school is directly related to the ideas of inclusive education and will allow to enrich modern ideas on the processes of socialpedagogical support and management of this category of children.